Pengaruh Mulsa terhadap Serangan Hama pada Tanaman Terung (Solanum melongena L.) di Desa Timbangan Kecamatan Indralaya Utara Kabupaten Ogan Ilir - Arsi, Arsi; Gustiar, Fitra; Pratama, Rahmat; SHK, Suparman; Hamidson, Harman; Umayah, Abu; Gunawan, Bambang; Pujiastuti, Yulia; Riansyah, Wanda Helmi; Djulian, Dhanillo; Muhari, Muhari (Seminar Nasional Lahan Suboptimal, 2022)
Arsi A, Gustiar F, Pratama R, SHK Suparman, Hamidson H, Umayah A, Gunawan B, Pujiastuti Y, Riansyah WH, Djulian D, Muhari M. 2022. The effect off mulch on pest attack on eggplant (Solanum melongena L.) in village  Timbangan,  Subdisctrict Indralaya North, Ogan Ilir City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 1023-1032. Palembang: Penerbit dan Percetakan Universitas Sriwijaya (UNSRI).Eggplant is a type of vegetable that is favored by the community because besides having a good taste, it also contains lots of vitamins and nutrients. In eggplant cultivation, there are several obstacles that must be faced. This obstacle cannot be separated from the attack by plant pests. Plant damage caused by pests results in decreased production due to the growth and development phase of eggplant plants cannot grow and develop optimally. The purpose of this research is to determine the effect of technical culture on the types of pests, population and intensity of pest attacks on purple eggplant (Solanum melongena L.) in Timbangan Village, Indralaya Utara District, Ogan Ilir Regency. The method used includes determining the land, determining sample plots and sample plants, as well as observing population numbers and intensity of pest attacks. The research was conducted in two eggplant fields with different plant ages. The population number and intensity of pest attacks were analyzed using the t test at the 5% confidence level. The pests found in eggplant are Spodoptera litura, Cheilomenes sexmaculata, and Atractomorpha crenulata. Statistical analysis shows that there are significant differences in the two fields due to different cultivation techniques.